LIFE HISTORY AND LARVAL PERFORMANCE OF THE COMMON GULL BUTTERFLY CEPORA NERISSA (LEPIDOPTERA: RHOPALOCERA: PIERIDAE) - S. P. VENKATA RAMANA; J. B. ATLURI; D. SANDYA DEEPICA; V. PRASANNA KUMAR; S. APPALA NAIDU (The Bioscan, 2011)
The Common gull butterfly Cepora nerissa is multivoltine and breeds throughout the year with higher frequency during July-December in the vegetations of North costal Andhra Pradesh. The life cycle period completes in 21-28 days. The growth of larvae was directly correlated with the quality food consumed. Food utilization efficiencies across the instars indicated that the approximate index (AD) values and growth rate (GR) decreased among subsequent instars starting from the first, Consumption index (CI) showed a continuous decrease with the increasing age of the larvae. The efficiency of conversion of digested food (ECD) and efficiency of conversion of ingested food (ECI) values continuously increased. The adults utilized several floral species as nectar resources while Caparis spinosa served as a larval host.